Analisis perbandingan perencanaan strategis pada perbankan syariah - Susanto, Rosya Mawaddah; Sholihah, Mar’atus; Fadhilah, Fairuz (Maliki Interdisciplinary Journal, 2023)
This study conducted a comparative analysis of strategic planning at three leading Islamic banks in Indonesia: Bank Syariah Indonesia (BSI), Bank Bukopin Syariah, and Bank BCA Syariah. The purpose of this study is to discover and compare various aspects of strategic planning used by the three banks, including profile, vision, mission, and strategy plan. Research methodology involves analyzing annual reports, analyzing journals, analyzing articles, and also visiting the official web site. The results showed that the three Islamic banks differed in terms of strategic planning. BSI prioritizes customer service and strengthening Islamic values in their business. Bank Bukopin Syariah's main focus is to improve operations and expand its market reach. Meanwhile, to gain a competitive advantage, Bank BCA Syariah focuses on product and service innovation.